2011
DOI: 10.1080/09723757.2011.11886145
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Genetic and Molecular Factors Responsible for Recurrent Pregnancy Loss

Abstract: Recurrent pregnancy loss usually results from disorders that cause intrauterine fetal damage, such as maternal or paternal chromosomal abnormalities. About 15 to 20 percent of all recognized pregnancies end in a first-trimester spontaneous abortion. Parents who are carriers of structural abnormalities have a higher risk of miscarriage because of the aberrations in genetic information may not segregate properly into the reproductive cells. This may be due to translocations, inversions, deletions, and duplicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…Two cases of autosomal balanced translocation were detected; one with 46,XY,t (13;14)(q14;p11) karyotype in azoospermic male and another 46,XY,t (8;12)(p23;q15) karyotype in oligospermic male. The structural chromosome autosomal abnormalities in men often lead to low sperm concentrations, abnormal sperms with male infertility and increased miscarriages [18]. Three cases of oligospermic males with Robertsonian translocation, two with 45,XY,t (13;14) karyotype and one with 45,XY,t (15;22) karyotype were detected in our study.…”
Section: Resultsmentioning
confidence: 71%
“…Two cases of autosomal balanced translocation were detected; one with 46,XY,t (13;14)(q14;p11) karyotype in azoospermic male and another 46,XY,t (8;12)(p23;q15) karyotype in oligospermic male. The structural chromosome autosomal abnormalities in men often lead to low sperm concentrations, abnormal sperms with male infertility and increased miscarriages [18]. Three cases of oligospermic males with Robertsonian translocation, two with 45,XY,t (13;14) karyotype and one with 45,XY,t (15;22) karyotype were detected in our study.…”
Section: Resultsmentioning
confidence: 71%
“…One of the major problems of pregnancy is miscarriage or RPL (Recurrent Pregnancy Loss).The most common types of abortion is spontaneous miscarriage with two or more sequential fetus loss. So far, several factors such as genetic disorders, hormonal, anatomical, oxidative stress, and environmental factors have been identified that are introduced as decisive and influential recurrent miscarriage reasons [1]. Among genetic variants involved in abortion, alterations in blood coagulation factors are reported to be important [10].…”
Section: Discussionmentioning
confidence: 99%
“…Fertility problems affect a large number of couples throughout the world.One of the most common form of these problems is abortion [1,2]. Miscarriage is known as the termination of pregnancy before the fetus development completes and be able to survive [3].…”
Section: Introductionmentioning
confidence: 99%
“…Other autosomal dominant mutated genes, such as those associated with myotonic dystrophy, thanatophoric dysplasia, and type II osteogenesis imperfecta, are also involved. Also, a subset of X-linked recessive lethal traits presents in a heterozygous form that is unnoticed in apparently phenotypically normal individuals and may result in RM (Chaithra et al, 2011). In addition, strong evidence supported the role of heritable thrombophilic disorders in the pathogenesis of reproductive failure.…”
Section: Single Gene Disordersmentioning
confidence: 99%